Pengembangan Media Pembelajaran E-Modul Perawatan Rambut Hair Mask pada Mata Kuliah Perawatan, Pratata, dan Penataan Rambut - Indah Cahyani Putri; Mari Okatini Armandari; Lilis Jubaedah (Journal on Education, 2024)
This study aims to develop a hair mask hair care E-Module as a systematic and interactive learning media for students of the Cosmetology Education Study Program. The method used is Research and Development (R&D) with the ADDIE model, including needs analysis, design, development, implementation, and evaluation. The validity test conducted by material and media experts showed significant improvement in the aspects of systematics, function, and product design. This E-Module provides comprehensive information on hair care techniques and can be accessed through mobile devices and computers, thus increasing students' motivation to learn. The total score obtained from the material expert validity test was 75% and the score from the media expert was 95% so that it could be categorized as a “Feasible” product. Thus, this research can be a reference in curriculum development and learning methods in the Cosmetology Education Study Program.